Factores sociodemográficos de los habitantes del barrio Jipiro Alto y su influencia en la utilización de los servicios de salud - Rueda Aponte, Evelyn Mariana (2022)
The use of health services is a complex issue that begins when people need to be healed and ends when elements start to satisfy this need; however, there are multiple variables that condition their use, both at the individual as well as collective; having knowledge on this matter constitutes the starting point for improving the quality of the service provided and the user's perception. The Centro de Salud No. 3 (CSN 3) of Loja, is a primary health care center serving the citizens, which constitutes the entry to the health system, therefore it is the basis to determine the characteristics and determining sociodemographic factors in this reasearch. The results of this study, show the sociodemographic data, as well as the perception of the quality of customer support received at Centro de Salud No. 3. These data were evaluated by the population of Jipiro Alto neighborhood. This research managed to identify factors that determine the variabilities in the evaluations of quality, related to the attention given to these people. These evaluations were directed to the age group with the greatest representation, such as users between 46 and 64 years old (49%, n=88), being the group of women (58%) who attend this health center more frequently. These data were analyzed through a sociodemographic survey which required 11 equitable questions. That survey was applied to 179 users of the Centro de Salud No. 3. The instrument used for verification was the SERVQUAL service quality measurement survey (multidimensional scale), which revealed a high level of satisfaction in relation to the 21 questions of the questionnaire that showed 66% (associated value) in the satisfactory and very satisfactory level on the Likert measurement scale. It’s also revealed that those results are related to the place, type of care, type of service and who they receive the support from. The perception of the user, under these parameters is positive, although they expect greater commitment from those who work at Centro de Salud No. 3 in Jipiro Alto neighborhood. Indirect evidence could also suggest that there are deficiencies in some other areas at Centro de Salud No. 3 which demonstrate negative attitude of the user, that must be solved